PENYULUHAN DAN PRAKTEK PIJAT BAYI PADA BAYI DI DESA MANUNGGANG JAE KECAMATAN PADANG SIDEMPUAN TENGGARA KOTA PADANG SIDEMPUAN TAHUN 2022: COUNSELING AND TRAINING FOR BABY MASSAGE TO BABY IN MANUNGGANG JAE VILLAGE, PADANG SIDEMPUAN SOUTHEAST DISTRICT PADANG SIDEMPUAN CITY ON 2022 - -, Nurhayati SST, MKM - (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
COUNSELING AND TRAINING FOR BABY MASSAGE TO BABY IN MANUNGGANG JAE VILLAGE, PADANG SIDEMPUAN SOUTHEAST DISTRICT PADANG SIDEMPUAN CITY ON 2022 NURHAYATI Lecturer in the D-III Midwifery Study Program at the Central Midwifery Academy Nurhayatihasibuan77@yahoo.com ABSTRACT Baby Massage is a technique that can be applied in optimizing baby's growth and development. optimization Given the importance of sleep time for the development of the baby, the need for sleep must really be met so as not to adversely affect its development. The need for sleep is not only seen from the aspect of quantity but also quality. If the quality of the baby's sleep is good, the baby's growth and development can be achieved optimally. One way that can be used to meet these needs is with baby massage. Babies who are massaged will be able to sleep soundly, while when they wake up, their concentration power will be fuller. One way is Baby Massage. The purpose of implementing this community service is to add insight to the community, especially mothers during their productive age, especially mothers who have babies, so they can better understand the benefits of doing baby massage to help improve the development and growth of babies. The material used in this Community Service is the lecture method and direct practice of carrying out baby massage to babies. The results of the implementation found that mothers who had baby massage said that they felt a change in their baby's sleep patterns, where after the massage their babies slept more soundly than usual. The conclusion obtained from the implementation of the lecture and practice method is that mothers in the village of Manunggang Jae have not been able to do massage for their babies themselves, so it is hoped that with the counseling and practice provided by mothers and also health cadres they can better understand baby massage techniques and be able to do it yourself without the help of others to their babies. Keywords: Infant Massage, sleep quality, counseling and practice